(untitled) (Journal of Asian Development Studies, 2026)
Objective of this research was to assess the role of community based organizations in the process of development of Northern Khyber Pakhtunkhwa, Pakistan. The data was collected from a total of 120 randomly selected households in three purposively selected villages, through face to face interview with the help of a pre-tested structure questionnaire. Findings of the study revealed that the local community based organization has a positive impact on the socio-economic status of the local people and greater participation of the local people in the development projects can have a sustainable impact on their socio-economic status. Therefore, greater role shall be given to these neighborhood organizations in the development projects for maintaining sustainability in the development projects.